Analysis of Genotype-Phenotype Correlations in Patients With Degenerative Dementia Through the Whole Exome Sequencing - Sun, Lin; Zhang, Jianye; Su, Ning; Zhang, Shaowei; Yan, Feng; Lin, Xiang; Yu, Jie; Li, Wei; Li, Xia; Xiao, Shifu (Frontiers in Aging Neuroscience, 2021)
Abstract Background: Sporadic dementias generally occur in older age and are highly polygenic, which indicate some patients transmitted in a poly-genes hereditary fashion. Objective: Our study aimed to analyze the correlations of genetic features with clinical symptoms in patients with degenerative dementia. Methods: We recruited a group of 84 dementia patients, and conducted the whole exome sequencing (WES). The data were analyzed focusing on 153 dementia-related causing and susceptible genes. Results: According to the American College of Medical Genetics and Genomics (ACMG) standards and guidelines, we identified 4 reported pathogenic variants, PSEN1 c.A344G, APP c.G2149A, MAPT c.G1165A, and MAPT c.G742A, 1 reported likely pathogenic variant, PSEN2 c.G100A, 1 novel pathogenic variants, SQSTM1 c.C671A, and 3 novel likely pathogenic variants, ABCA7 c.C4690T, ATP13A2 c.3135delC, and NOS3 c. 2897-2A>G. 21 variants with uncertain significance in PSEN2, C9orf72, NOTCH3, ABCA7, ERBB4, GRN, MPO, SETX, SORL1, NEFH, ADCM10, SORL1 and etc. were also detected in AD or FTD patients. Conclusion: The new variants in dementia-related genes indicated heterogeneity in pathogenesis and phenotype of degenerative dementia. WES could serve as efficient diagnostic tool for detecting the intractable dementia.